Infección del carbón del maní según el momento de exposición de los clavos a las esporas - Paredes, Juan Andrés; Monguillot, Joaquín Humberto; Pérez, Ignacio Agustín; Rago, Alejandro Mario; Edwards Molina, Juan Pablo; Torres, A.M. (Asociación Argentina de Fitopatólogos, 2022)
Poster